Public Trust and Financial Transparency of E-Government Implementation in Bandung City - Dini Arwati; Dini Verdania Latif (Journal of Economics, Business, and Government Challenges, 2019)
Indonesia government, at the time, is now trying to implement e-government in each of the Organization. E-government is a technology and information-based system that aims to improve the function of public administration and relations with the public. With e-government, it hoped that information transparency would be created, especially financial information. A transparent system can prevent the misuse of the budget, which affects the high level of corruption. Survey results at the global level show that there are cases of fraud that cause distrust of the government. The study is intended to determine the level of trust of society towards transparency finance in e-government. The research method used is the descriptive method by distributing questionnaires to 200 people of Bandung residents. The results showed that financial transparency in e-government affected people's trust.